1976
DOI: 10.1073/pnas.73.8.2803
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K-dependent synthesis and modification of precursor prothrombin in cultured H-35 hepatoma cells.

Abstract: The ability of confluent monolayers of H-35 cells, originally obtained from a rat hepatoma, to synthesize prothrombin in response to vitamin K1 (phylloquinone) was studied. As demonstrated by radioimmunoassay, selective barium salt adsorption, and two coagulation assays which discriminate between precursor-and mature-prothrombin, these cells retained their ability to synthesize precursor prothrombin (preprothrombin) in the absence of exogenous phylloquinone (vitamin K). When phylloquinone was added to the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…This indicates that the extra "(-carboxyl groups of normal prothrombin are not available externally and are probably salt-linked to basic groups in the interior of the molecule. Munns et al (174) observed that confluent monolayers of H-35 hepatoma cells respond to vitamin K addition by the synthesis and secretion of mature prothrombin. As demonstrated by radioimmunassay, selective barium salt adsorption, and two coagulation assays that discriminate between precursor and mature prothrombin, these cells retained their ability to synthesize precur sor prothrombins in the absence of exogenous phylloquinone.…”
Section: Glycosylationmentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that the extra "(-carboxyl groups of normal prothrombin are not available externally and are probably salt-linked to basic groups in the interior of the molecule. Munns et al (174) observed that confluent monolayers of H-35 hepatoma cells respond to vitamin K addition by the synthesis and secretion of mature prothrombin. As demonstrated by radioimmunassay, selective barium salt adsorption, and two coagulation assays that discriminate between precursor and mature prothrombin, these cells retained their ability to synthesize precur sor prothrombins in the absence of exogenous phylloquinone.…”
Section: Glycosylationmentioning
confidence: 98%
“…The 10 Gla residues in fragment I are at positions 7,8, 15,17,20,21,26,27,30, and 33 . "precursor forms". In fact, multiple intermediate forms of immature prothrom bin have been found in the endoplasmic reticulum of vitamin K-deficient rats (59,94,174).…”
Section: Metabolism Of the Signal Sequencementioning
confidence: 99%
“…Previously published reports of in vitro studies have demon strated that vitamin K x treatment affects aspects of prothrombin synthesis in addition to γ-carboxylation. Vitamin K t treatment of rat hepatoma (H-35) cultures for 6 or 24 h resulted in a 2-or 5fold increase, respectively, in secreted prothrombin levels over control levels as measured by radioimmunoassay (13). Vit amin Kt treatment of human hepatoblastoma (HepG2) cultures for 24 h resulted in a 2-fold increase in secreted prothrombin over control levels as measured by radioimmunoassay (14).…”
Section: Introductionmentioning
confidence: 99%
“…The amino-terminal region of the precursor sequence was highly hydrophobic and probably corresponds to the signal sequence found in other secreted Little is known about the regulation of the prothrombin gene. Munns et al [31] de scribed a rat hepatoma cell line that, in the presence of vitamin K, synthesized and se creted functionally active prothrombin. Graves et al [32,33] [34] have studied the hepatic microsomal forms of rat prothrombin.…”
Section: Biosynthesis Of Prothrombinmentioning
confidence: 99%